Frequency dependence of hand-arm vibration on palmar sweating response - Ando, Hideo; Noguchi, Ryo; Ishitake, Tatsuya (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'This study attempted to elucidate the effects of hand-arm vibration frequency on palmar sweating response. ' ' METHODS ': 'Palmar sweating was measured before and during vibration exposure on the right palm of six healthy men. The left hand was exposed for 3 minutes to the following root mean square (rms) acceleration magnitudes and frequencies of vibration: 5 m/s2 at 31.5 Hz, 10 m/s2 at 63 Hz, 20 m/s2 at 125 Hz, 40 m/s2 at 250 Hz, and 50 m/s2 at 315 Hz. According to international standard ISO 5349, these vibration levels generate the same frequency-weighted acceleration magnitude of 2.5 m/s2 rms. A control condition consisted of grasping a handle without vibration. As the index of the activated central nervous system, plasma 3-methoxy-4-hydroxyphenylglycol (MHPG) was measured before and immediately after each vibration exposure.´ ' ' RESULTS ': 'Each condition of vibration induced a palmar sweating response. Among the six vibration conditions, vibration of 125 Hz and 63 Hz caused large palmar sweating responses compared with those of 315 Hz and the control condition. Plasma MHPG did not increase significantly after either vibration exposure. ' ' CONCLUSIONS ': 'The palmar sweating response to vibration with the same frequency-weighted acceleration magnitude suggested dependency on frequency. The study suggests that the somatosympathetic reflex is associated with different palmar sweating responses.
Keywords: acute vibration stress; frequency dependence; hand-arm vibration; palmar sweating response; somatosympathetic reflex; vibration frequency